2002
DOI: 10.1142/s0219581x02000917
|View full text |Cite
|
Sign up to set email alerts
|

Stretching of Single Dna Molecules by Langmuir–blodgett Method

Abstract: We propose a new method that double-stranded DNA molecules can be stretched and immobilized on the clean glass substrate by using a lipid monolayer at the air-water interface. This method is based on the substrate lifting of Langmuir-Blodgett method. We observed fluorescence images of polyion complex films with a scanning near-field optical microscope (SNOM). As a result, straight fluorescent lines aligned parallel to the lifting direction were observed and it was considered that isolated single DNA molecules … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…0.50 nm). 23 The length of segment B (1.5 mm) accorded well with the length of the ATpart estimated from the extension rate of d(AT)10 templateprimers. These results indicate that segment B corresponded to the AT-part in the DNA block copolymer.…”
supporting
confidence: 72%
See 2 more Smart Citations
“…0.50 nm). 23 The length of segment B (1.5 mm) accorded well with the length of the ATpart estimated from the extension rate of d(AT)10 templateprimers. These results indicate that segment B corresponded to the AT-part in the DNA block copolymer.…”
supporting
confidence: 72%
“…4 shows an AFM image and height histogram of the platinum deposited DNA block copolymer stretched and immobilized on a mica substrate by the LB method. 11,23,24 We produced the height histograms from cross-sectional images of the AFM image shown in Fig. 4(a).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We have found that when a DNA-amphiphile polyion complex monolayer, which is formed at the air-water interface, was transferred to a glass substrate using the Langmuir-Blodgett (LB) method, DNA molecules could be immobilized on the glass substrate in a stretched configuration [10,11]. The stretching direction of the DNA molecules is parallel to the lifting direction of the substrate.…”
Section: Introductionmentioning
confidence: 99%